The serpent gift - Kaaberbol, Lene (The Shamer chronicles, 2006)
As her brother Davin is unjustly confined to a prison and looks for a way to escape, Dina, now twelve years old, meets her father and learns that she may share his serpent gift of the ability to give people dreams.